CELLULOSE ACETATE FILM AND METHOD FOR PRODUCING CELLULOSE ACETATE FILM - KONNO, Haruo; SHIMAMOTO, Shu; URAKI, Yasumitsu (2022)
An object of the present disclosure is to provide a cellulose acetate film having excellent bending properties and high transparency. The subject cellulose acetate film contains cellulose acetate having a cellulose triacetate I crystal structure, the cellulose acetate film having a light transmittance of 70% or higher at 660 nm.